Anti-tumour necrosis factor antibody treatment does not change serum levels of cortisol binding globulin in patients with rheumatoid arthritis but it increases androstenedione relative to cortisol. Issue 9 (11th February 2005) - Straub, R H; Sarzi-Puttini, P; Atzeni, F; Buttgereit, F; Carrabba, M; Cutolo, M
Abstract : Background: Cortisol binding globulin (CBG) is produced by liver cells and is inhibited by proinflammatory cytokines such as interleukin (IL) 6. CBG serum levels are typically low during prolonged inflammatory processes. Thus, observed changes of cortisol during anti-tumour necrosis factor (TNF) treatment may be related to changes of CBG in rheumatoid arthritis (RA). Objective: To investigate the course of CBG during anti-TNF treatment in RA. Methods: 13 patients with longstanding RA, without prior prednisolone treatment, were included in this longitudinal study with subcutaneous adalimumab. Results: Treatment with anti-TNF markedly decreased clinical markers of inflammation and serum IL6. Serum levels of cortisol, CBG, and the ratio of cortisol/CBG did not change markedly, whereas the ratio of serum CBG/IL6 increased (p = 0.004). In parallel, levels of adrenocorticotropic hormone decreased during the observation period. The ratio serum androstenedione/serum cortisol increased during the study (p = 0.036). Conclusions: During anti-TNF treatment relatively normal levels of CBG and a normal ratio of CBG/cortisol are found. Changes of cortisol in relation to IL6 during anti-TNF treatment, seen previously, may not be related to changes of CBG.